Implementation of Hospital Occupational Health and Safety Regulations to Minimize Occupational Accidents at the Sultan Agung Islamic Hospital, Semarang - Mayangkara, Radit H.; Subiyanto, Achmad Arman; Tamtomo, Didik Gunawan (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Sultan Agung Islamic Hospital Semarang, which is one of the providers in the health sector, has complex and continuous activities which in turn have the potential to cause various impacts and risks, such as work accidents, nosocomial infections, and occupational diseases. Therefore, more detailed observations are needed on the enforcement of occupational health and safety regulations to minimize these impacts. This study aims to determine the application of occupational health and safety hospital regulations to minimize work accidents at Sultan Agung Hospital, Semarang.Subjects and Method: This study was conducted using a qualitative approach. The key informants in this study were the Director of the Sultan Agung Islamic Hospital totaling 1 person and the supporting informants were the field staff of the Sultan Agung Hospital totaling 17 people. Data collection techniques were carried out by direct observation, questionnaires and focus group discussions. The data analysis technique used in this study is Narrative Analysis.Results: This study was conducted using a qualitative approach with data collection techniques by direct observation, questionnaires and focus group discussions.Conclusion: Regulations are still drawn up sectorally by various agencies that regulate occupational health and safety in hospital so that efforts to minimize the number of work accidents are quite difficult. Keywords: occupational health and safety, Sultan Agung Islamic Hospital, work accidentsCorrespondence: Radit Hartantyo Mayangkara. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: raditmayangkara@gmail.com. Mobile: (+62)8122938885.Journal of Health Policy and Management (2021), 06(03): 160-167https://doi.org/10.26911/thejhpm.2021.06.03.01